2007
DOI: 10.1152/ajpregu.00424.2006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sex hormones on renal estrogen and angiotensin type 1 receptors in female and male rats

Abstract: Although the mechanisms are not understood, evidence suggests that 17beta-estradiol (E2) confers protection from cardiovascular and renal complications in many diseases. We have reported that E2 decreases angiotensin type 1 receptors (AT1Rs) in different tissues and hypothesize that E2 exerts tonic inhibition on AT1Rs, reducing effects of ANG II. This study determined the effects of E2 and dihydrotestosterone (DHT) on cortical estrogen receptors (ERs) and glomerular AT1R binding in rats. Animals underwent sham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 46 publications
3
70
0
2
Order By: Relevance
“…Our laboratory confirmed by mRNA and western analysis the expression of ER and ER subtypes [52]. Previous studies found that total kidney and mesangial cell ER expression are regulated by the level of estrogens [14,[67][68][69]]. This appears to be the case for podocyte ER expression.…”
Section: Of Podocyte Estrogen Receptors By Esupporting
confidence: 79%
“…Our laboratory confirmed by mRNA and western analysis the expression of ER and ER subtypes [52]. Previous studies found that total kidney and mesangial cell ER expression are regulated by the level of estrogens [14,[67][68][69]]. This appears to be the case for podocyte ER expression.…”
Section: Of Podocyte Estrogen Receptors By Esupporting
confidence: 79%
“…Rogers et al (105), studying the role of sex hormones in expression of components of renal renin angiotensin in healthy SpragueDawley rats, have suggested that an estrogen-mediated attenuation of renal AT 1 binding is a potential mechanism by which estrogen exerts protection from vascular and renal disease in females (105). When this inhibition is lifted following ovariectomy in their model, or in diabetes or menopause, the resulting increased ANG II signaling increases both the degree of susceptibility to vascular and renal disease and the rate of existing disease progression (105).…”
Section: Potential Mechanisms Underlying Sex Differences In Developmementioning
confidence: 99%
“…We recently published that greater levels of the vasodilatory peptide ANG (1-7) contribute to sex differences in the hypertensive response to chronic ANG II infusion in spontaneously hypertensive rats (SHR), although it is unknown whether there are additional molecular mechanism(s) contributing to sex differences in the blood pressure response to ANG II. Activation of angiotensin type 1 (AT 1 ) receptors mediate most well-known biological functions of ANG II, including the stimulation of oxidative stress, and female SHR have fewer AT 1 receptors than male SHR (43). However, little is known regarding the relative contribution of ANG II-mediated oxidative stress on blood pressure regulation in male vs. female rats.…”
mentioning
confidence: 99%